2003
DOI: 10.1103/physreva.67.052303
|View full text |Cite
|
Sign up to set email alerts
|

Fast, efficient error reconciliation for quantum cryptography

Abstract: We describe a new error reconciliation protocol Winnow based on the exchange of parity and Hamming's "syndrome" for N −bit subunits of a large data set. Winnow was developed in the context of quantum key distribution and offers significant advantages and net higher efficiency compared to other widely used protocols within the quantum cryptography community. A detailed mathematical analysis of Winnow is presented in the context of practical implementations of quantum key distribution; in particular, the informa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
127
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 25 publications
0
127
0
1
Order By: Relevance
“…For high-loss lines, our protocol is at present limited by the reconciliation efficiency, but its intrinsic performances remain very high. Since most of the limitations of the present proof-of-principle experiment appear to be of a technical nature, there is still a considerable margin for improvement, both in the hardware (increased detection bandwidth, better homodyne efficiency, lower electronic noise), and in the software (better reconciliation algorithms [26] , see Appendix A). In conclusion, the way seems open for implementing the present proposal at telecommunications wavelengths as a practical, high bit-rate, quantum key distribution scheme over long distances.…”
mentioning
confidence: 99%
“…For high-loss lines, our protocol is at present limited by the reconciliation efficiency, but its intrinsic performances remain very high. Since most of the limitations of the present proof-of-principle experiment appear to be of a technical nature, there is still a considerable margin for improvement, both in the hardware (increased detection bandwidth, better homodyne efficiency, lower electronic noise), and in the software (better reconciliation algorithms [26] , see Appendix A). In conclusion, the way seems open for implementing the present proposal at telecommunications wavelengths as a practical, high bit-rate, quantum key distribution scheme over long distances.…”
mentioning
confidence: 99%
“…In addition, it skips detection of even multiple bits of error in each iteration. These withhold it in terms of efficiency [24,36,44]. For optimum performance, research has shown that block size of eight bits will minimize number of iterations required and amount of bit exposed [36].…”
Section: Winnow Protocolmentioning
confidence: 99%
“…In Winnow protocol, for an erroneous 7-bit block of sifted key that shows diverging parity during preliminary test, the difference between syndrome of the block of sifted key deduced by Alice and the one deduced by Bob, when computed by Bob during syndrome measurement to determine the associated correctable error pattern before the most probable single-bit error correction can be performed by Bob [24,36]. The reconciliation, which is complemented by privacy maintenance, is shown in Fig.…”
Section: The Proposed Sp 1985 Reconciliation System Architecturementioning
confidence: 99%
See 2 more Smart Citations